2007
DOI: 10.1534/genetics.107.080564
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Heterosis for Growth-Related Traits in Arabidopsis Investigated by Testcross Progenies of Near-Isogenic Lines Reveals a Significant Role of Epistasis

Abstract: Epistasis seems to play a significant role in the manifestation of heterosis. However, the power of detecting epistatic interactions among quantitative trait loci (QTL) in segregating populations is low. We studied heterosis in Arabidopsis thaliana hybrid C24 3 Col-0 by testing near-isogenic lines (NILs) and their triple testcross (TTC) progenies. Our objectives were to (i) provide the theoretical basis for estimating different types of genetic effects with this experimental design, (ii) determine the extent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 54 publications
3
92
3
2
Order By: Relevance
“…Three of these showed overdominance although the traits, with heterosis levels ranging from À1.83 to 49.4%, were nonreproductive. In a second study in Arabidopsis with two reciprocal libraries of near-isogenic lines (NILs) (Melchinger et al 2007b) 56 QTL for seven growth-related traits were mapped using the method described in Semel et al (2006). The majority of the QTL showed overdominance but by a novel approach on generation means analysis using triple testcrosses of the NILs the authors were able to show that the seemingly overdominant gene action at many of the QTL was due to a combination of partial to full dominance effects and additive 3 additive epistatic interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of these showed overdominance although the traits, with heterosis levels ranging from À1.83 to 49.4%, were nonreproductive. In a second study in Arabidopsis with two reciprocal libraries of near-isogenic lines (NILs) (Melchinger et al 2007b) 56 QTL for seven growth-related traits were mapped using the method described in Semel et al (2006). The majority of the QTL showed overdominance but by a novel approach on generation means analysis using triple testcrosses of the NILs the authors were able to show that the seemingly overdominant gene action at many of the QTL was due to a combination of partial to full dominance effects and additive 3 additive epistatic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis Kusterer et al (2007a) found a significant role of epistasis in the expression of heterosis while analyzing generation means and variance components for biomass-related traits in a triple-testcross design with a recombinant inbred line population. Furthermore, in a study on QTL mapping in Arabidopsis using NIL libraries Melchinger et al (2007b) found about three times more loci with significant additive 3 additive epistatic interactions with the genetic background than with dominance effects. Since according to Melchinger et al (2007a) heterosis is determined by the dominance effects of QTL and the sum of their additive 3 additive epistatic interactions, this study again indicates a strong role of epistasis in the expression of heterosis in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…S15), with the caveat that any correlation based on a large number of small-effect loci may be obscured by the moderate-effect size loci that we detected in the GWA studies. Several previous studies of heterosis using controlled crosses in A. thaliana have identified loci that exhibit all possible modes of gene action, including additive, dominant, and epistatic interactions (26)(27)(28)(94)(95)(96). Lack of support for the major heterosis hypotheses comes also from studies in crop species, particularly in maize and rice.…”
Section: Arabidopsis Thaliana In the Context Of Traditional Heterosismentioning
confidence: 99%
“…Finally, the pseudooverdominance hypothesis also explains heterosis with the complementation of recessive alleles but proposes that when linked in repulsion, such alleles appear overdominant. Outside of these classical hypotheses, some cases of hybrid inferiority (19)(20)(21)(22) and hybrid superiority (23)(24)(25)(26)(27)(28)(29)(30) have been linked to epistatic interactions between parental alleles.…”
mentioning
confidence: 99%
“…Although there have been a large number of genetic analyses in plants with results favoring one hypothesis or another (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), genetic composition pertaining to heterotic performance of crop hybrids has not been fully characterized in an experimental population. There has been no assessment about the relative contributions of these genetic components to heterosis in a crop hybrid.…”
Section: Epistasis | Recombinant Inbred Intercrossmentioning
confidence: 99%